Exact solutions for clamped spherical and cylindrical panels via a unified formulation and boundary discontinuous method - (:unkn) unknown (Elsevier BV, 2024)
Numerous works in both recent and historical literature have concentrated on formulating theories to perform static analysis on simply-supported shell structures. However, it is worth noting that obtaining analytical solutions for clamped boundary condit...
Keywords: Paneles esféricos; Método de Fourier